Public Goods, Fiscal Gaps, and Road Decay in Lampung: A Political Economy Perspective - Anggraini, Yenita; Kartini, Dede Sri (Universitas Pattimura, 2025)
This article examines the relationship between fiscal disparity and road infrastructure damage as a reflection of local government performance in Lampung Province. Using a descriptive qualitative approach, the study draws on secondary data from official government documents, local media reports, and academic literature. Thematic analysis was applied to identify patterns of governance weaknesses, fiscal structures, and the dynamics of infrastructure policy implementation. The findings reveal that widespread road damage in Lampung is not merely a technical issue, but a systemic governance failure rooted in fiscal constraints and suboptimal public service delivery. Fiscal imbalance is evident in low local revenue, the dominance of personnel expenditure, and heavy dependence on central transfers without proportional compensation for national burdens such as logistics flows and inter-island transportation. Local institutions, including regional-owned enterprises (BUMD) and public service agencies (BLUD), remain underutilized as alternative revenue sources. This study positions road quality as a direct indicator of governance effectiveness. Its novelty lies in integrating public goods theory, governance theory, and fiscal disparity frameworks to analyze infrastructure problems in structural and political terms. Policy reforms should include national fiscal arrangements based on service burdens, local fiscal capacity strengthening, and institutional revitalization to support equitable and sustainable infrastructure provision.